IDDF2019-ABS-0140 Attenuation of diethylnitrosamine induced hepatic cancer in wistar albino rats by madhuca longifolia extract via knockdown oxidative stress and inflammation. (June 2019) - Singh, Manvendra
Abstract : Background: Hepatocellular cancer occurred due to hepatocytes damage and inflammation. Interleukin as a pleiotropic cytokine in the immune system plays a pivotal role in the onset and progression of tumours . Emphasizing on approach to down-regulate the cytokines might be an effective boon for the treatment of hepatocellular carcinoma. Madhuca longifolia used as a traditional plant in the treatment of hepatocellular carcinoma. So focused on this scrutiny, we evaluate the therapeutic potential of the aqueous extract of Madhuca longifolia in Diethylnitrosamine induced hepatic cancer in Wistar albino rats. Methods: To determine the effect of aqueous extract of Madhuca longifolia leaf following Diethylnitrosamine exposure, the antioxidant activity was measured by the enzymatic and non-enzymatic antioxidants. In addition Proinflammatory cytokines and inflammatory mediators, namely TNF-a, IL-1b, IL-10 and NF-kb were also assessed. Results: The finding of the current study reveals that DEN treatment significantly downregulated the content of antioxidant parameter (SOD, catalase, GPx, GSH, G6PD and vitamin C) and upregulated the level of proinflammatory cytokines. Administration of aqueous extract of Madhuca longifolia attenuated the antioxidant parameter, cytokines and inflammatory mediators in rats. Conclusions: These study clearly highlight the chemopreventive prospective of Madhuca longifolia aqueous extract against DEN-induced Hepatic cancer by knockdown oxidative stress and inflammation.